Plastic Interactions with Pollutants and Consequences to Aquatic Ecosystems: What We Know and What We Do Not Know - Fernanda Cássio; Daniela Batista; Arunava Pradhan (Biomolecules, 2022)
Plastics are a group of synthetic materials made of organic polymers and some additives with special characteristics. Plastics have become part of our daily life due to their many applications and uses. However, inappropriately managed plastic waste has raised concern regarding their ecotoxicological and human health risks in the long term. Due to the non-biodegradable nature of plastics, their waste may take several thousands of years to partially degrade in natural environments. Plastic fragments/particles can be very minute in size and are mistaken easily for prey or food by aquatic organisms (e.g., invertebrates, fishes). The surface properties of plastic particles, including large surface area, functional groups, surface topography, point zero charge, influence the sorption of various contaminants, including heavy metals, oil spills, PAHs, PCBs and DDT. Despite the fact that the number of studies on the biological effects of plastic particles on biota and humans has been increasing in recent years, studies on mixtures of plastics and other chemical contaminants in the aquatic environment are still limited. This review aims to gather information about the main characteristics of plastic particles that allow different types of contaminants to adsorb on their surfaces, the consequences of this adsorption, and the interactions of plastic particles with aquatic biota. Additionally, some missing links and potential solutions are presented to boost more research on this topic and achieve a holistic view on the effects of micro- and nanoplastics to biological systems in aquatic environments. It is urgent to implement measures to deal with plastic pollution that include improving waste management, monitoring key plastic particles, their hotspots, and developing their assessment techniques, using alternative products, determining concentrations of micro- and nanoplastics and the contaminants in freshwater and marine food-species consumed by humans, applying clean-up and remediation strategies, and biodegradation strategies.